Detection of human immunodeficiency virus type 1 transmitted drug resistance among treatment-naive individuals residing in Jakarta, Indonesia - Siti Qamariyah Khairunisa; Ni Luh Ayu Megasari; Retno Pudji Rahayu; Adiana Mutamsari Witaningrum; Shuhei Ueda; Muhammad Qushai Yunifiar M; Dwi Wahyu Indriati; Tomohiro Kotaki; Adria Rusli; Nasronudin; Masanori Kameoka (Infectious Disease Reports, 2020)
The presence of transmitted drug resist- ance (TDR) in human immunodeficiency virus type 1 (HIV-1) infected individuals naive to antiretroviral therapy, may affect the effectiveness of treatment. Jakarta, the capital city of Indonesia, recorded the high- est number of cumulative HIV infection cases in the country. This study aimed to identify on the appearance of TDR, as well as to identify HIV-1 subtypes circulating among treatment-naive individuals in Jakarta. Whole blood samples collected from 43 HIV-1 infected, treatment-naive individuals. Viral subtyping and drug resist- ance testing were performed on HIV-1 pol genes amplified using nested polymerase chain reaction. CRF01_AE was detected most frequently in Jakarta (73.08%). Drug resistance-related major mutation was not detected in protease fragments of pol gene, but two major mutations, K103N (6.67%) and Y181C (6.67%), were detected in reverse transcriptase fragments of pol gene. Our results suggest that TDR was emerged in Jakarta at a certain extent, thus further surveillance study to monitor the TDR prevalence and circulating HIV-1 subtypes in this region is considered to be necessary.